Potency of Sago Palm (Metroxylon spp.) as an Alternative for Raw Material of Biofuel - M. SYAKIR; ELNA KARMAWATI (Perspektif, 2013)
Indonesia is a country having the largest area of sago in the world. Sago is plant producing carbohydrate used as raw material of ethanol, therefore it has the largest potency to produce bio-ethanol as fossil fuel substitution. In the past, development of sago plantation was still in a forest, with 95% area located in the East of Indonesia as the rest is in the West. The productivity is varies depends on age and location with tha average of 90 to 700 kg per stem. If the productivity is 100 kg per stem with the population of 30 stems per ha, the total sago starch in Indoensia will be 6,84 millions ton per year. The constrains in development are plant material and cultivation technology, therefore their research and dissemination need to be increased. Beside to produce bioethanol, sago forest can absorb CO2 emission from tidal swamp, therefore Indonesia can earn carbon-trade compensation.   Keywords : Sago, potency, bioethanol, CO2 emission, superior varieties.